2022
DOI: 10.1111/ddg.14819
|View full text |Cite
|
Sign up to set email alerts
|

DNA chip‐based diagnosis of onychomycosis and tinea pedis

Abstract: Summary Background and objectives Onychomycosis (OM) and tinea pedis (TP) are common fungal infections. Currently, diagnosis is based on direct microscopy and culture that have a low to moderate sensitivity and/or require up to 3–4 weeks until results are obtained. PCR techniques have emerged for the diagnosis of fungal infections, but little is known about their sensitivity and specificity in diagnosing. Here, we compared the diagnostic value of a DNA‐chip technology, that detects 56 fungal pathogens, in a si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 34 publications
0
6
0
Order By: Relevance
“…Because EBA is such a rare disease, we believe that implementation of preventive measures based on the identification of risk factors is, for the most part, impracticable. For example, the identified EBA risk factors dermatophytosis and candidiasis are common diseases ( 26 ). The effort to screen for EBA in these patient populations would not justify the potential benefit.…”
Section: Discussionmentioning
confidence: 99%
“…Because EBA is such a rare disease, we believe that implementation of preventive measures based on the identification of risk factors is, for the most part, impracticable. For example, the identified EBA risk factors dermatophytosis and candidiasis are common diseases ( 26 ). The effort to screen for EBA in these patient populations would not justify the potential benefit.…”
Section: Discussionmentioning
confidence: 99%
“…More recently, a DNA-chip assay of the clinical specimen has been developed that allows rapid diagnosis of tinea pedis. 86 In the DNA-chip assay, fungal DNA is amplified by using multiplex polymerase chain reaction with subsequent determination by hybridization on a microarray chip. 86 The DNA-chip assay has a high sensitivity (90.7%).…”
Section: Reviewmentioning
confidence: 99%
“… 86 In the DNA-chip assay, fungal DNA is amplified by using multiplex polymerase chain reaction with subsequent determination by hybridization on a microarray chip. 86 The DNA-chip assay has a high sensitivity (90.7%). 86 The sensitivity can be further increased to 96.3% by factoring results from microscopic examination of KOH wet-mount preparation or direct immunofluorescence microscopy.…”
Section: Reviewmentioning
confidence: 99%
“…In addition, morphological interspecies differentiation can be difficult in some cases such as T. indotineae, T. mentagrophytes, and T. interdigitale, and in general, requires great experience for accurate identification [95,96]. Molecular diagnostic methods, on the other hand, are becoming a more preferable option, as they can provide quicker and more accurate results [97]. Although this may require special training and advanced equipment, the benefits of utilizing such techniques outweigh this hurdle.…”
Section: Management Prospective and Alternative Treatmentsmentioning
confidence: 99%
“…Several methods have been used in this regard including polymerase chain reaction (PCR) based on internal transcribed spacer (ITS) sequencing, real-time PCR, DNA microarray, and next-generation sequencing [98]. Currently, studies have shown that the best accuracy can be obtained by using both conventional and molecular techniques [97]. Thus, incorporating molecular techniques into routine diagnosis of dermatophytosis can help in overcoming the limitations of the traditional methods.…”
Section: Management Prospective and Alternative Treatmentsmentioning
confidence: 99%